2019
DOI: 10.1016/j.jtho.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Non–Small Cell Lung Cancer and Brain Metastases Treated with Checkpoint Inhibitors

Abstract: Disclosure: Dr. Hendriks reports research funding from Roche and Boehringer Ingelheim (both to her institution), fees for participation in advisory boards of Boehringer Ingelheim (to her institution) and BMS (to her institution and to her personally), travel/conference reimbursement from Roche and BMS (to her personally), participation in a mentorship program with key opinion leaders that was funded by AstraZeneca, and fees for educational webinars from Quadia outside of the submitted work. Dr. Audigier-Valett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
156
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 43 publications
12
156
4
2
Order By: Relevance
“…In total, 346 potentially relevant citations were reviewed (Figure 1). Ultimately, 16 studies published from 2009 to 2019 that reported OS and/or PFS data were included in the final analysis [17,[19][20][21][22][27][28][29][30][31][32][33][34][35][36][37]. The total number of patients included was 4045 ranging from 45 to 1025 patients per study (median, 151).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 346 potentially relevant citations were reviewed (Figure 1). Ultimately, 16 studies published from 2009 to 2019 that reported OS and/or PFS data were included in the final analysis [17,[19][20][21][22][27][28][29][30][31][32][33][34][35][36][37]. The total number of patients included was 4045 ranging from 45 to 1025 patients per study (median, 151).…”
Section: Resultsmentioning
confidence: 99%
“…Brain metastases are not confirmed as a negative prognostic factor because ICIs may cross the blood-brain barrier and induce disease response in selected patients [31]. Data from both retrospective series [36] and clinical trials showed good activity of ICIs as a single agent [37] or in combination with chemotherapy [38] in patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study retrospectively investigated the prognostic impact of the presence of BMs in routine clinical care as well as clinical trials. 21 The cohort included 1025 NSCLC patients who had received anti PD-1/PD-L1 Ab with or without anti-cytotoxic T-lymphocyte antigen 4 (anti-CTLA-4), and multivariate analysis included the following factors: age, smoking status, histology, number of organs with metastases, line of treatment, PS, use of corticosteroids, and the presence of BMs. The study showed that the presence of BMs was not a significant factor for PFS and OS.…”
Section: Discussionmentioning
confidence: 99%